Pengaruh Pembelajaran Online Terhadap Prestasi Belajar Siswa SMP Al-Falah Bekasi - Sebrina, Nikita; Putri, Eka (Universitas Indraprasta PGRI, 2021)
Home learning or E-learning is done to break the chain of spread of the covid-19 virus. This study aims to find out the influence of Online Learning (X) on Learning Achievement (Y) in eight grade of SMP Al-Falah Bekasi student in social sciences learning. This research method uses Descriptive Survey. The research sample used a random sampling sample of 71 students. The conclusion of the results revealed: 1) The regression liner regression equation obtained Y= 57.683 + 0.238X means that the Y score can be predicted through linear equations. 2) From the results of the analysis, it can be inferred that Online Learning affects learning achievements. This can be seen from thit and p- value is smaller than 0.05. Therefore, it can be presented that the influence of Online Learning has a positive effect on learning achievements. 3) From the results of the analysis of the regression equation signification test obtained that thit and p-value is smaller than 0.05 or Ho is rejected. Thus the regression of Y or X is significant or Online Learning has an effect on the Learning Achievement of social science major. 4)The correlation coefesien signification test obtained= 0.224 with a small p-value of 0.05 which means Ho is rejected. Thus, the coefesien is moderately correlated between Online Learning and Social science major Learning Achievement.Â Whereas from the results of the analysis obtained RSquere 0.520, which means that 52% variation of variables results of Online Learning Against Learning Achievement